2012
DOI: 10.1080/00207594.2012.702215
|View full text |Cite
|
Sign up to set email alerts
|

Health performance of individuals within the Campbell paradigm

Abstract: In this paper, we developed a comprehensive health performance measure that formally links individual health attitudes with the likelihood of engaging in a wide variety of health-related behaviours from various domains such as sustenance, hygiene, and physical exercise. Within what Kaiser, Byrka, and Hartig (2010) call the Campbell paradigm, we equated general health attitude with what a person does to retain or promote his or her health. Thus, health behaviours, on one hand, were expected to form a homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Whereas much of current attitude research draws on evaluative statements (for a recent discussion, see Otto, Kröhne, & Richter, ), classic conceptions such as Rosenberg and Hovland's tripartite model of attitude () suggest that behavioral self‐reports can be valid indicators of people's attitudes. In a recent empirical test, Kaiser, Merten, and Wetzel () have shown that the behavioral items from the General Ecological Behavior scale (e.g., “I bring empty bottles to a recycling bin”)—our attitude measure in the present research—along with 48 evaluative and normative statements (e.g., “Bringing empty bottles to a recycling bin is good … bad ”) can be combined in a single, Rasch‐homogenous scale of indicators to assess people's environmental attitude (for parallel evidence from another attitude domain see Byrka & Kaiser, ).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas much of current attitude research draws on evaluative statements (for a recent discussion, see Otto, Kröhne, & Richter, ), classic conceptions such as Rosenberg and Hovland's tripartite model of attitude () suggest that behavioral self‐reports can be valid indicators of people's attitudes. In a recent empirical test, Kaiser, Merten, and Wetzel () have shown that the behavioral items from the General Ecological Behavior scale (e.g., “I bring empty bottles to a recycling bin”)—our attitude measure in the present research—along with 48 evaluative and normative statements (e.g., “Bringing empty bottles to a recycling bin is good … bad ”) can be combined in a single, Rasch‐homogenous scale of indicators to assess people's environmental attitude (for parallel evidence from another attitude domain see Byrka & Kaiser, ).…”
Section: Methodsmentioning
confidence: 99%
“…Decades after it was initially proposed, Campbell's idea has made a resurgence in psychology as a theoretical framework termed the 'Campbell paradigm' (Kaiser et al 2010;Byrka and Kaiser 2013;Urban 2016). The Campbell paradigm conceptualizes the performance of a behaviour as a combined function of the situational threshold (behavioural difficulty or costs) associated with the realization of the behaviour and the level of a person's attitude or disposition to pursue the attitudinal goal reflected by the behaviour (Kaiser et al 2010).…”
Section: Attitude Measurement Using the Campbell Paradigmmentioning
confidence: 99%
“…where the natural logarithm of the ratio of the probability of person k's engagement (pki) relative to the probability of non-engagement (1pki) in a specific behaviour i is given by the difference between k's attitude level (θk) and the difficulty of the behaviour (δi) (Byrka 2009;Kaiser et al 2010). In this mathematical representation, people are distinguishable with respect to their attitudes (regardless of the behavioural indicators considered in the measurement procedure), and behaviours are distinguishable by how difficult they are to realize (irrespective of the persons considered; Kaiser et al 2013).…”
Section: Operationalizing the Campbell Paradigmmentioning
confidence: 99%
“…Recognizing an attitude therefore requires the empirical identification of a set of behaviors that represent what people commonly do to implement the strength of a specific personal attitude (e.g., toward organ donation; see Figure 1). Note that empirically identifying sets of behaviors that are—due to their costs—transitively ordered is not a trivial matter as it can fail (for typical successful examples, see [11,12,13]).…”
Section: Identifying Attitudesmentioning
confidence: 99%